2015
DOI: 10.1096/fj.15-270421
|View full text |Cite
|
Sign up to set email alerts
|

Generation and characterization of a trackable plant-made influenza H5 virus-like particle (VLP) containing enhanced green fluorescent protein (eGFP)

Abstract: Medicago, Inc. has developed an efficient virus-like particle (VLP) vaccine production platform using the Nicotiana benthamiana expression system, and currently has influenza-based products targeting seasonal/pandemic hemagglutinin (HA) proteins in advanced clinical trials. We wished to generate a trackable HA-based VLP that would allow us to study both particle assembly in plants and VLP interactions within the mammalian immune system. To this end, a fusion protein was designed, composed of H5 (from influenza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 67 publications
(103 reference statements)
0
11
1
Order By: Relevance
“…A 1-h temporal difference in the administration of VP6T and NoV VLPs impaired the adjuvant effect dramatically, further supporting the role of rVP6 as a delivery vehicle. It has been published that particulate antigens travel very quickly, in terms of minutes, from the site of injection to the local lymphoid tissue [46]. Although this study does not extend to confirm this, the results suggest that RV VP6 and VLPs may form aggregates when coformulated, VP6 functioning as a carrier.…”
Section: Discussioncontrasting
confidence: 66%
“…A 1-h temporal difference in the administration of VP6T and NoV VLPs impaired the adjuvant effect dramatically, further supporting the role of rVP6 as a delivery vehicle. It has been published that particulate antigens travel very quickly, in terms of minutes, from the site of injection to the local lymphoid tissue [46]. Although this study does not extend to confirm this, the results suggest that RV VP6 and VLPs may form aggregates when coformulated, VP6 functioning as a carrier.…”
Section: Discussioncontrasting
confidence: 66%
“…First, they have all of the advantages of nanoparticulate vaccines in terms of antigen protection, presentation and efficient delivery [20, 31]. We have recently shown that plant-derived VLPs bearing influenza H5 injected into the footpad of a mouse can be found in ~10% of the dendritic cells of the draining lymph node in ~10 minutes [32]. They cluster and activate human immune cells through HA-sialic acid interactions to elicit powerful innate responses in human peripheral blood mononuclear cells within minutes in vitro [21].…”
Section: Discussionmentioning
confidence: 99%
“…(27,28) and on the growing body of evidence that the plant-made VLPs stimulate the immune response in a different way than split vaccines. For instance, we have recently shown that these VLPs rapidly access draining lymph nodes (29), where they associate with and activate immune cells, including B cells, macrophages, and dendritic cells (30). Furthermore, these vaccines elicit balanced humoral and cellular responses in both preclinical (young mice and ferrets) and clinical studies in healthy young adults (10)(11)(12)31).…”
Section: Discussionmentioning
confidence: 99%